Effect of Electroacupuncture on Short-Chain Fatty Acids in Peripheral Blood after Middle Cerebral Artery Occlusion/Reperfusion in Rats Based on Gas Chromatography–Mass Spectrometry. (23rd August 2022) - Ke, Xiaohua; Xiang, Qing; Jiang, Pingli; Liu, Weilin; Yang, Minguang; Yang, Yihan; Shi, Dan; Chen, Lidian; Tao, Jing
Abstract : Previous fundamental and clinical research has shown that electroacupuncture (EA) at the acupoints of Quchi (LI11) and Zusanli (ST36) can successfully alleviate motor dysfunction following stroke. Additionally, it has been discovered that gut microbiota and their metabolites play an essential role in stroke. However, the relationship between the metabolites of gut microbiota and the efficacy of EA is still unclear. Therefore, the aim of this study was to evaluate the mechanism of EA at LI11 and ST36 in the treatment of motor dysfunction after middle cerebral artery occlusion/reperfusion (MCAO/R) in model rats by comparing the differences and correlation between different short-chain fatty acids (SCFAs) and the recovery of motor function. The results indicated that EA at LI11 and ST36 acupoints enhanced the neurological function, motor function, and infarct volume of MCAO/R rats. The levels of acetic acid, propionic acid, and total SCFAs were considerably lower in the MCAO/R group than in the sham group (P < 0.05 ). Acetic acid, propionic acid, and total SCFA concentrations were substantially higher in the MCAO/R + EA group than in the MCAO/R group (P < 0.05 ). Finally, Pearson correlation analysis revealed that the propionic acid concentration was substantially favorably connected with the duration on the rotarod (r = 0.633 and P < 0.05 ) and highly negatively correlated with the modified neurological severity score (mNSS) (r = − 0.698 and P < 0.05 ) and the percentage of cerebral infarct volume (r = − 0.729 and P < 0.05 ). Taken together, these findings indicate that the increase in propionic acid may be one of the mechanisms and targets of EA at LI11 and ST36 acupoints to improve poststroke motor dysfunction in MCAO/R rats.